2015
DOI: 10.1109/temc.2015.2410834
|View full text |Cite
|
Sign up to set email alerts
|

Transient Lightning Impulse Performance Analysis for Composite Transmission Line Tower

Abstract: In this paper, the transient impulse performances of a 330-kV composite transmission line tower under direct lightning strokes are comprehensively presented. An equivalent distributed parameter model combined with lumped capacitance elements for the tower is established. The wave impedances of the hybrid model are determined by using analytic equations. The lumped capacitances are calculated by 3-D finite element method (FEM). An accurate model for extended grounding structure (EGS) of the tower base consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
(26 reference statements)
0
11
0
Order By: Relevance
“…Using a composite transmission line tower by double grounding the conductor system [25] Flashover will not happen for negative or positive injected lightning current…”
Section: Methods Advantages Disadvantagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a composite transmission line tower by double grounding the conductor system [25] Flashover will not happen for negative or positive injected lightning current…”
Section: Methods Advantages Disadvantagesmentioning
confidence: 99%
“…It was demonstrated in Reference [24] that reducing the soil resistivity and permittivity decreases the rate of power outages by 13-32% for usual distributions. A composite transmission line was applied by Reference [25]; the results showed that the best structure is a double-grounding conductor system, as flashover will not happen in this structure with either negative or positive lightning current. It was also found that the radius of the grounding conductors had little effect on improving lightning performance.…”
Section: Introductionmentioning
confidence: 99%
“…Huangfu et al. considered the coupling between the ground conductors of the composite tower and established a non‐uniform multi‐conductor transmission line model combined with lumped circuit elements, and finally formed a composite transmission line tower model under lightning strike [17, 18]. Ishii et al.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the transmission tower model is an effective tool on both the lightning protection level and the lightning protection design of the transmission line. Thus, in recent years, a large number of researchers have carried out modelling studies on transmission towers [5], which can be roughly divided into the single-wave impedance model [6][7][8][9][10][11][12][13][14], frequency-dependent model [15,16] and multi-wave impedance model [17][18][19][20][21][22][23][24][25]. Among them, the multi-wave impedance models are mainly divided into the composite tower equivalent model [17,18], multilayer transmission tower model (MTTM) [19][20][21][22] and Hara model [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation